2021
DOI: 10.1002/star.202100211
|View full text |Cite
|
Sign up to set email alerts
|

Composition and Quality of Low‐Fat Halloumi Cheese Made Using Modified Starch as a Fat Replacer

Abstract: The use of modified maize starch as a fat replacer in low‐fat Halloumi cheese is investigated. Halloumi cheese is made from cow milk (3.5% fat) or from partially skimmed cow milk (1% fat) with 1%, 2%, and 3% modified starch. The addition of modified starch to cow's milk decreased rennet coagulation time and curd syneresis but increased curd tension. The modified starch addition also increased yield and total nitrogen but decreased pH, total solids, fat, ash, and total volatile fatty acids. Total bacterial coun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 13 publications
(11 reference statements)
2
5
0
Order By: Relevance
“…The addition of modified starch to cow milk improved the sensorial properties, yield, and protein content. In addition, it decreased the fermentation time, pH, total solids, fat, ash, and total volatile fatty acids, as well as total bacterial count and lipolytic bacteria [130]. Sesame seeds (0-6%) used as fat replacers increased total solid, fat, and acidity but decreased the protein and ash contents in Labneh [131].…”
Section: Increasing and Unifying Quality Parametersmentioning
confidence: 95%
See 2 more Smart Citations
“…The addition of modified starch to cow milk improved the sensorial properties, yield, and protein content. In addition, it decreased the fermentation time, pH, total solids, fat, ash, and total volatile fatty acids, as well as total bacterial count and lipolytic bacteria [130]. Sesame seeds (0-6%) used as fat replacers increased total solid, fat, and acidity but decreased the protein and ash contents in Labneh [131].…”
Section: Increasing and Unifying Quality Parametersmentioning
confidence: 95%
“…It was also reported that the partial substitution of 30% of cow milk with camel milk to make low-fat Akkawi improved the rheological properties during the storage period [129]. Low-fat Halloumi was made by using modified maize starch as a fat replacer [130]. The addition of modified starch to cow milk improved the sensorial properties, yield, and protein content.…”
Section: Increasing and Unifying Quality Parametersmentioning
confidence: 96%
See 1 more Smart Citation
“…The rate of TVFA accumulation increased with increasing the storage time in both control and partially purified enzyme treatments. Other authors also noticed a gradual increase in TVFA contents during the storage period which might be due to increasing the lipolysis rate [ 57 ]. It was clear that cheese made by the purified B. subtilis MCE had more volatile flavor compounds compared to the control, and this could be due to the high lipolytic activity of the coagulant.…”
Section: Discussionmentioning
confidence: 99%
“…Hydrocolloids are also used for the preparation of cheese analogues to improve their structural properties. For instance, a low-fat Halloumi cheese prepared using modified maize starch as a fat replacer showed improved textural and sensory properties while decreasing the period of rennet coagulation, compared to control cheese (Basiony and Hassabo, 2022). In another study, the effect of native and modified starch was compared as a fat replacer in the preparation of cheese.…”
Section: Carbohydrates As a Fat Replacermentioning
confidence: 99%